Image database with synchronized sensor data for vision based navigation systems - Rathnayake, C.; Rajakaruna, N.; Murray, Iain (2014)
© 2014 IEEE. Image databases are becoming an important element of the emerging information technologies. They have been used in a wide variety of applications such as geographical information systems, computer-aided design and manufacturing systems, multimedia libraries, and medical image management systems. This research will investigate storage methodologies for an image database with synchronized inertial measurement unit (IMU) data and Meta Information of the images. As images are usually taken under the different environmental and physical conditions like low lighting and shadow conditions and blurring, an image database is necessary to be created with meta data of the images and the IMU data which are collected during the image capturing process, in order to investigate image enhancement mechanisms. This database can be used for the research projects currently which may be used to construct maps for use in mobility and navigation and to an analysis of resultant images of novel algorithms use in navigation.